SETTLEMENT OF CONSUMER DISPUTES BY CONSUMER DISPUTE RESOLUTION AGENCY - Vivi Hayati (Jurnal Hukum Samudra Keadilan, 2024)
Consumer dispute resolution outside the court through the Consumer Dispute Settlement Agency (BPSK) has become an increasingly important alternative in Indonesia's consumer protection legal system. This study aims to analyse the legal framework and the effectiveness of the BPSK in resolving disputes between consumers and businesses. The methodology used is a normative juridical approach, conducting literature studies on relevant laws and regulations, legal literature, and BPSK decisions. The results show that BPSK has a strong legal basis in the Consumer Protection Act, but there are several obstacles in its implementation, such as limitations in executorial authority and inconsistencies in legal interpretation. In conclusion, although BPSK has the potential to be an effective dispute resolution mechanism, regulatory improvements and institutional strengthening are needed to enhance legal certainty and consumer protection in Indonesia.